2015
DOI: 10.1021/acs.jpcc.5b05302
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Limits of d-Band Center Theory: Electronic and Electrocatalytic Properties of Pd-Shell–Pt-Core Nanoparticles

Abstract: Theoretical DFT calculations suggest that chemisorption energy, activation barrier, and energy of dissociation of small molecules on metal surface can be correlated to the d-band center of gravity of that metal. This holds true for many systems and reactions, but there are also reports where significant discrepancies were found. Here we present the critical assessment of applicability of the d-band center theory to nonuniform catalytic systems, such as core−shell nanoparticles. For Pt-core−Pd-shell nanoparticl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
103
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(111 citation statements)
references
References 30 publications
6
103
2
Order By: Relevance
“…It has been reported that the Pt core‐level (CL) binding energy is highly sensitive to d ‐band structure . and the Pt 4f 7/2 CL binding energy shift is a good indicator (“fringerprint”) for the shift of the occupied d ‐band center .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been reported that the Pt core‐level (CL) binding energy is highly sensitive to d ‐band structure . and the Pt 4f 7/2 CL binding energy shift is a good indicator (“fringerprint”) for the shift of the occupied d ‐band center .…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the Pt core-level (CL) binding energy is highly sensitive to d-band structure. [12] and the Pt 4f 7/2 CL binding energy shift is a good indicator ("fringerprint") for the shift of the occupied d-band center. [37] So X-ray photoelectron spectroscopy (XPS) was used to investigate the Pt electronic state in PtAg/graphene, which greatly influenced its catalytic performance.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…But in many cases, the direction of charge transfer is different. For example, in PtPd systems, the electronic effect is usually stated as the charge transfer from Pd to Pt [589]; however, in core-shell-structured Pt@Pd catalysts for ethanol oxidation, the direction of the charge transfer is from Pt to Pd [595]. Here, it would appear that the direction of the charge transfer is not completely determined by the electronegativity difference of the two metals.…”
Section: Electronic Effectmentioning
confidence: 99%